DEEP LEARNING FROM A PARTICIPATORY ASSESSMENT APPROACH BASED ON STUDENT EMPOWERMENT: A CASE STUDY IN HIGHER EDUCATION - Cisternas, Marisol del Carmen Alvarez; Flores, Margarita del Rosario Yau; Castillo, Myrna Lilian Alvarez (Veredas do Direito, 2026)
This study examines the impact of assessment strategies that foster deep learning within a transformational model focused on student empowerment. Deep learning is understood as students’ ability to build meaningful understanding, think critically, and transfer knowledge across contexts. Transformational assessment shifts attention from summative judgment to practices that promote continuous learning, reflection, and active participation. Student empowerment involves learners taking responsibility for selecting evidence, interpreting expectations, and using analytical rubrics to guide their performance. A qualitative–descriptive intrinsic case study was conducted with 20 university students participating in a learning experience based on transformational assessment. Data were collected from reflections, discussions, and analyses of assessment tasks using an inverse planning model and analytical rubrics, then coded thematically. Findings show that students strengthened critical and reflective skills by questioning and analyzing their own assessment tasks. Through inverse planning, they identified relevant evidence and exercised autonomy in assembling it according to rubric criteria. These strategies allowed them to move beyond memorization toward deeper understanding, critical analysis, and problem solving. The study suggests that empowerment-oriented assessment promotes autonomy and higher-order thinking, supporting efforts to enhance teaching quality. It demonstrates that assessment can become a transformative learning experience, positioning students as active and reflective agents in their educational development.